2012
DOI: 10.1159/000338661
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Idiopathic Dilatation of the Right Atrium: Antenatal Appearance, Postnatal Management, Long-Term Follow-Up and Possible Pathomechanism

Abstract: Introduction: Idiopathic dilatation of the right atrium (IDRA) is a rare abnormality usually detected by chance at any time between antenatal and adult life. It is defined as isolated enlargement of the right atrium in the absence of other cardiac lesions causing right atrial dilatation. IDRA can be associated with atrial arrhythmia and systemic embolism. The clinical presentation shows high variability ranging from the lack of any symptoms up to cardiac failure. Methods/Results: We describe 2 children with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
1
15
0
5
Order By: Relevance
“…2 It is believed to be congenital. 3 Our demonstration of fetal right atrial dilation supports this belief. This suggests an early fetal insult or phenomenon that leads to dilation of the right atrium.…”
supporting
confidence: 80%
“…2 It is believed to be congenital. 3 Our demonstration of fetal right atrial dilation supports this belief. This suggests an early fetal insult or phenomenon that leads to dilation of the right atrium.…”
supporting
confidence: 80%
“…Right atrial enlargement is an idiopathic condition that has been reported from fetal life to the elderly (2,3,4). It is also known by other terms such as congenital aneurysm or diverticulum of the right atrium(2, 4, 7)Prenatal diagnosis has the bene t of identifying fetuses with cardiac abnormality (1,3)and termination of the pregnancy have been proceeded in some cases (5). also, there were cases diagnosed with older ages while they were asymptomatic for a longer period (1, 3, 4, 6), the outcomes of some patients diagnosed with congenital right atrial aneurysm were accompanied by the life-threatening conditions, such as atrial tachycardia, thromboembolism, respiratory distress, and atrial arrhythmia(3)such conditions require more consideration and attention in patients follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Right atrial diverticulum also known as by the other names such as the idiopathic dilatation of right atrium(IDRA) (1,2), right atrial aneurysm(RAA)(3), or even aneurysm of the right atrial appendage (4,5), is a rare a condition which most often diagnosed by chance in adults (2,4), but the prenatal and antenatal diagnosis of this condition has been reported even more rarely. (1,3)while IDRA or RAA de ned as the isolated enlargement of the right atrium without the presence of any other cardiac lesions which can cause right atrium dilatation, a diverticulum is a bromuscular strand entry of the right atrium and it is important from this aspect that can be misdiagnosed with right atrial aneurysm which involves all layers(epicardium, myocardium, and endocardium) of the atrial wall, while it is better this two conditions to be differentiated from each other (1,6)in the literature, this differential diagnostic border has not been clearly established and that's why we see these two different terms are used frequently instead of each other as we can see in Morrow et al report (7). Other misdiagnoses such as Ebstein's anomaly should be ruled out using fetal heart echocardiography (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…The wall thickness of RA is homogenous in IDRA such as in our case. Conversely, there is fibrous, saccular region and a paper-thin-wall in congenital RA aneurysm (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial description of IDRA in 1955, few cases have been reported in the medical literature, predominantly in adults (1-6). Hoffman et al (7) claimed that a functional partial anomalous pulmonary venous insertion may imitate a structural abnormal pulmonary vein connection in etiopathogenesis of this anomaly.…”
Section: Discussionmentioning
confidence: 99%